First flight - Baysura, Kelly, 1970- (Vero Beach, Fla. : Rourke, 2001)
Text and color photos provide basic information on the history of airplanes; also includes a glossary and a further reading list with Web sites.
Includes bibliographical references (p. 24) and index.
2.1
3-6
3-6
Library Talk
Keywords: Airplanes -- Juvenile literature; Flight -- Juvenile literature; Airplanes; Flight; Airplanes; Flight